2022
DOI: 10.1111/aos.15092
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic inner foveal layer as a factor associated with metamorphopsia after vitrectomy for epiretinal membrane

Abstract: Purpose To analyse the relationship between the extent of metamorphopsia and optical coherence tomography (OCT) parameters including the ectopic inner foveal layer (EIFL) in patients with epiretinal membrane (ERM) who underwent pars plana vitrectomy (PPV). Methods This study included 63 eyes of 62 patients who underwent PPV for ERM. Metamorphopsia was assessed by measuring the metamorphopsia score for vertical lines (MV) and metamorphopsia score for horizontal lines (MH) using M‐CHARTS. Central retinal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, Yanagida et al reported that there was a significant relationship between EIFL thickness and metamorphopsia scores both preoperatively and postoperatively. [14] In this study, we observed that postoperative EIFL thickness decreased significantly, BCVA (LogMAR), MH, and MV decreased significantly compared to the preoperative period. However, we found no correlation between BCVA, MH, MV, and EIFL thickness neither in the preoperative nor in the postoperative period.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Furthermore, Yanagida et al reported that there was a significant relationship between EIFL thickness and metamorphopsia scores both preoperatively and postoperatively. [14] In this study, we observed that postoperative EIFL thickness decreased significantly, BCVA (LogMAR), MH, and MV decreased significantly compared to the preoperative period. However, we found no correlation between BCVA, MH, MV, and EIFL thickness neither in the preoperative nor in the postoperative period.…”
Section: Discussionmentioning
confidence: 49%
“…[13] Yanagida et al reported that there was a significant relationship between EIFL thickness and metamorphopsia scores both preoperatively and postoperatively. [14] To the best of our knowledge, both stage 3 and stage 4 ERMs have been included in studies on this subject, including the studies mentioned above. The retinal structure is disrupted in stage 4 ERMs.…”
mentioning
confidence: 99%